Perbedaan Minat Mengikuti Organisasi pada Mahasiswa Program Studi Psikologi dan Ilmu Komunikasi Universitas ‘Aisyiyah Yogyakarta - Putri, Risma Della; Ariyanto, Mustaqim Setyo; Salim, Agus (VISA: Journal of Vision and Ideas, 2024)
This study aims to identify differences in organizational interests between Psychology and Communication Science students at Universitas 'Aisyiyah Yogyakarta. With a quantitative approach and comparative design, data were obtained through a questionnaire involving 184 students from both study programs. The results of the analysis using the Mann-Whitney test showed that Communication Science students had a higher interest in organizing than Psychology students. This difference is thought to be influenced by internal and external factors, such as the need to expand social networks and develop communication skills in Communication Science students. These findings are expected to be a reference for institutions in designing more appropriate organizational development programs for students from various study programs, according to their respective needs and interests.